Novas tecnologias de gestão na Petrobras: os papeis da atitude competitiva e das estratégias empresariais no processo de adoção de inovações - Salles, Washington Luiz Faria (2001)
The present research investigates the influence of competitive attitude and strategic issues on the processes that concur to stimulate the adoption of innovation in a Company. On the basis of the effected bibliographical walk through that included the studies on innovation process, organizational learning, enterprise strategy, competitive advantage and competitive attitude, a theoretical construct with 03 independent variables and 02 dependent variables, that had been correlated to attain the research objective, was proposed. To develop the empirical test of the model, questionnaires were sent to 400 managers and supervisor of Petrobras, the Brazilian Oil Company. Had been gotten indices of rollback of about 40% with relation to the total of the universe and 58% on total of the managers of the company. Data were statistically evaluated using the model of structural relations (LISREL), that allowed the measure of how much the competitive attitude and the competitive advantage influence the disposal of the companies in adopting new managerial technologies. The findings partially support the hypotheses on the influence of the competi tive attitude on the disposal in adopting and investing in managerial innovations. The findings present, also, some impossibilities to interpret how much the competi tive advantage is related with innovation, due the difficulty of managers in identifying which the enterprise strategies consists or will consist in advantage regarding the competition between the companies.